Divergence of annual and perennial species in the Brassicaceae and the contribution of cis-acting variation at FLC orthologues - Kiefer, Christiane; Karl, Robert; Koch, Marcus (Molecular ecology, 2017)
Variation in life history contributes to reproductive success in different environments. Divergence of annual and perennial angiosperm species is an extreme example that has occurred frequently. Perennials survive for several years and restrict the duration of reproduction by cycling between vegetative growth and flowering, whereas annuals live for 1 year and flower once. We used the tribe Arabideae (Brassicaceae) to study the divergence of seasonal flowering behaviour among annual and perennial species. In perennial Brassicaceae, orthologues of FLOWERING LOCUS C (FLC), a floral inhibitor in Arabidopsis thaliana, are repressed by winter cold and reactivated in spring conferring seasonal flowering patterns, whereas in annuals, they are stably repressed by cold. We isolated FLC orthologues from three annual and two perennial Arabis species and found that the duplicated structure of the A. alpina locus is not required for perenniality. The expression patterns of the genes differed between annuals and perennials, as observed among Arabidopsis species, suggesting a broad relevance of these patterns within the Brassicaceae. Also analysis of plants derived from an interspecies cross of A. alpina and annual A. montbretiana demonstrated that cis-regulatory changes in FLC orthologues contribute to their different transcriptional patterns. Sequence comparisons of FLC orthologues from annuals and perennials in the tribes Arabideae and Camelineae identified two regulatory regions in the first intron whose sequence variation correlates with divergence of the annual and perennial expression patterns. Thus, we propose that related cis-acting changes in FLC orthologues occur independently in different tribes of the Brassicaceae during life history evolution.